Pelatihan dan Pembuatan Laporan Keuangan Berbasis Aplikasi Makna Pos pada Bumdes Sari Makmur Klaten - Gustita Arnawati Putri; Yoppi Syahrial; Indri Sri Endarwati; Rohana Wanaswati; Elma Putri Utami (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The Village Ownership Enterprise Agency (BUMDes) has been recognised since 2004 in the Act No. 32 section 213, one of which reads "The village can establish the village ownership enterprise according to the needs and potential of the village". BUMDes is known to be around 19 years old and has been operating in various areas including Sukoharjo and Klaten. BUMDes in a village usually have more than one business unit and have been operating for a long time. However, the problem lies in the business unit that owns not only one and does not have an effective and efficient financial reporting tool.The solution offered to solve the problems faced by partners is to create an application-based system similar to MaknaPos or SiApik to help BUMDes manage their finances and make their financial reports well. The objective is that the financial report submitted can make it easier for my stakeholders to know the progress of the BUMDes.